REPRESENTASI PESAN ANTI NARKOBA DALAM LIRIK LAGU â€œLINTING DAUNâ€ (ANALISIS SEMIOTIKA FERDINAND DE SAUSSARE) - Aisyah Pratiwi; Aisya Aisya; Haminudin Haminudin (MEDIOVA: Journal of Islamic Media Studies, 2022)
This study aims to determine the representation of anti-drug messages in the lyrics of the song "Linting Daun". The song as a literary work is often used as a medium of communication to convey a certain message which usually has a correlation between the lyrics of the song and the reality that is happening. This research uses semiotic analysis from Ferdinand de Saussure. In this analysis, there are several stages carried out, namely: (1) determining the sign from the lyrics of the song "â€œLinting Daunâ€" as the object of research, (2) writing a signifier or physical form, namely the lyrics of the song "â€œLinting Daunâ€", (3) write a sign (signified), (4) see between signs, sign forms, and sign concepts with social reality in the form of references or external reality. This study explains how the anti-drug message is voiced through a song with a beautiful tone notation so that not only the meaning can be taken, but the beautiful song can also entertain everyone who listens to it so that the anti-drug message to be conveyed is more easily accepted by various groups.